Examining The Factors Affecting Tax Avoidance Indications: A Case Of Energy Companies In Indonesia - Reshanggono, Awindya Kalma; Asalam, Ardan Gani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Taxes are contributions from individual and corporate taxpayers that are compelling for the state's prosperity. However, companies attempted to minimize their tax expenses, while the government is against actions that potentially reduce state revenue. Companies that commit this action are referred to as tax avoidance. Tax avoidance has been committed by Adaro Energy, part of the Indonesia’s energy sector companies. Therefore, a study is necessary to determine whether leverage, earnings management, and fiscal loss compensation affect tax avoidance in energy companies for 2017-2021. In this study, purposive sampling was utilized to select samples. The final sample consisted of 11 companies or 55 sample data. In E-views 12, panel data regression was used to analyze data. The results showed that earnings management negatively affects tax avoidance. However, leverage and fiscal loss compensation do not affect tax avoidance. This study is anticipated to inform readers and companies to be more cautious in earnings management utilization and income-decreasing pattern.